Influence of the focusing characteristics of near-infrared lasers on the maintenance of plasma luminescence - Zhou, Lian; Chen, Yi; Guo, Xin; Shi, Yan; Zhao, Tianqi; Zhan, Chunlian; Jin, Shangzhong (Frontiers in Physics, 2022)
The interaction of 980-nm continuous laser radiation with the plasma of a continuous optical discharge in xenon lamps at a pressure of p = 12 atm has been studied. The threshold power and characteristics of the laser required to sustain the xenon plasma became our focus. According to the theory of Gaussian beam propagation, the laser parameters after collimation and focusing are obtained by combining ZEMAX simulation and the actual measurement. The influence of the beam waist ω0, which determines the power density distribution at focus, and the Rayleigh range Z0, which determines the energy concentration range, on the threshold maintenance power is expounded. The results show that there is a threshold power density for the generation of plasma, whose value is about 1,500–2,000 W/mm2, and that the threshold maintenance power of the plasma shows an overall decreasing trend with decreasing ω0. When ω0 is reduced to a higher power density that can easily maintain the thermodynamic equilibrium process of the plasma, the mismatch between Z0 and the plasma size caused by the decrease in Z0 makes the threshold power tend to be stable and increasing.